“Man darf nicht sagen...”. Kafka’s 1906 fragment Über ästhetische Apperception („On Perception“) (Materiali di Estetica. Terza serie, 2017)
Inspired by Scott Spector’s analysis of the Prague Circle, this article investigates how Kafka’s fragment “On Perception” (“Über ästhetische Apperception”) might be viewed as a product of the dialogue between Brod and Kafka. After surveying how Kafka scholars have framed and tried to apply Kafka’s early text on aesthetics, the article shows Kafka’s work refuses to engage with the powerful anti-Jewish tropes of aesthetic theory around 1900 (Weininger) and instead develops literary themes and techniques that anticipate many aspects of Kafka’s later literary production.Keywords: Kafka; Brod; Herbart; apperception; modernity; Weininger; Jews; antisemitism